POTENSI LIMBAH POPOK BAYI SEBAGAI MATRIKS PENGONTROL PELEPASAN PUPUK UREA PADA TANAMAN CABAI - Nurfika Ramdani; Mariaulfa Mustam; Hijrah Amaliah Azis (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
The problem of disposable diaper waste is a serious problem that challenges the environment. Therefore, the researchers sought the utilization of diaper waste in agriculture. Efficiency of fertilizer absorption in plants in the environment by 30-40%, remaining in the air and evaporating into ammonia gas. Utilization of baby diaper waste as a matrix and urea as a filler was carried out in this study. This is expected to be able to control the release of nitrogen in fertilizers in accordance with the amount and amount needed by plants (desorption) and maintain nitrogen requirements in the soil, so that the amount of fertilizer given is more efficient than conventional methods. How the purpose of this research is how to make fertilizer based on diaper waste, determine Nitrogen adsorption capacity into the matrix and determine the fertilizer requirements for growing chilli seedlings. The study was divided into 5 stages, the processing of baby diaper waste; second, the manufacture of urea larvae (fillers); three, filling the filler into the matrix; Rate, determine the Nitrogen adsorption capacity into the matrix; discuss, test on plants. The research results obtained are variations in the contribution of urea used as fillers is 15%. Based on this research, it can be said that diaper waste has the potential to control the release of urea. Furthermore, it can explain the rate of release of urea in chili plants.